Penerapan Goal-Free Problems dalam Pembelajaran Matematika secara Kolaboratif untuk Melatih Kemampuan Siswa dalam Memecahkan Masalah - Dimas Bagus Setiawan; Susanah Susanah (Program Studi S1 Matematika UNESA, 2023)
This study aims to (1) describe the application of teachers in carrying out mathematics learning with collaborative learning using the Goal-Free Problems strategy. (2) describe student activities while participating in collaborative learning with a goal-free problems strategy. (3) describe students' ability to solve problems after implementing collaborative learning with a goal-free problems strategy. (4) describes students' extraneous cognitive load when applying collaborative learning models with goal-free problems strategies. This research is a descriptive study with a quantitative approach that was carried out in class VIII F of SMP Muhammadiyah 2 Taman. The research instruments used included teacher activity observation sheets, student activity observation sheets, student problem-solving ability test questions, and student response questionnaires. The results showed that the observation of the application of learning by the teacher obtained an average score of 3.81 with very good criteria; student activity obtained a total score of 89.88%, which is classified as active during learning; students' ability to solve problems is classified as good because they get a classical mastery percentage of 79.31%; and 8 out of 10 student response statements got good and very good responses.